Problem Based Learning Model Based on Tat Twam Asi for Understanding Natural Science Concepts - I Made Sujana; Desak Putu Parmiti; I Made Citra Wibawa (Universitas Pendidikan Ganesha, 2023)
Science can be a provision for students to face various challenges in the global era. This research aims to test the effect of the Problem-Based Learning (PBL) learning model based on Tat Twam Asi on the understanding of science concepts for class V students. This research is a quasi-experimental research with a non-equivalent post-test-only control group design. The population in this study were all class V students. The sample for this study used a simple random sampling technique. The sample for this research was 36 students as the experimental group. Research data was collected using the test method with objective test instruments to measure understanding of science concepts. The data obtained were analyzed using descriptive and inferential statistics (t-test). The results of the research show that there is a difference in understanding of science concepts between students who follow the Problem-Based Learning (PBL) learning model based on Tat Twam Asi and students who do not follow the Problem-Based Learning (PBL) learning model based on Tat Twam Asi in class V. It is known that The Tat Twam Asi-based Problem Based Learning (PBL) learning model has a significant influence on fifth-grade students' understanding of science concepts.